Delineation of the dystonia-parkinsonism syndrome locus in Xq13. - Graeber, M B (1992)
The X chromosome-linked dystonia-parkinsonism syndrome (XDP) is a severe movement disorder, characterized by both dystonia and parkinsonism. XDP is a genetically homogeneous disorder. Known ancestry of all patients has been traced back to Panay, Philippines, where the disease probably originated from a single mutation (founder effect). The gene locus, DYT3, has been previously assigned to the proximal long arm of the X chromosome (Xq12-q21.1). Using four dinucleotide tandem repeat (DNTR) sequences from Xq13-derived yeast artificial chromosomes (YACs), we further delineate DYT3 within Xq13. Observation of a recombination event between DYT3 and DNTR locus 4548-7, derived from a YAC encompassing locus DXS56, establishes 4548-7 as a distal flanking marker. Assignment of DYT3 to a region in Xq13, flanked by loci 4548-7 and DXS159, is further supported by highly significant allelic association between DYT3 and a total of four DNTR loci--PY2-31, PY5-10, 4548-1, and 4548-7--located in a region defined by PGK1 and DXS56. /phi/ and /delta/ values were 0.82/0.35, 0.78/0.42, 0.65/0.34, and 0.88/0.58 for PY2-31, PY5-10, 4548-1, and 4548-7 at P less than 10(-2), P less than 10(-4), P less than 10(-3), and P less than 10(-6).